Babe - Cromwell, James; Szubanski, Magda; Cavanaugh, Christine; Noonan, Chris; Universal Pictures (Firm). ([Pace of production not identified] Universal Pictures, 1995)
"Babe, a pig raised by sheepdogs, learns to herd sheep with a little help from Farmer Hoggett"--https://www.imdb.com/title/tt0112431
Produced by Bill Miller, George Miller, Doug Mitchell; music by Nigel Westlake; cinematography by Andrew Lesnie.
James Cromwell, Magda Szubanski, Christine Cavanaugh.
DVD
In English.
Keywords: Drama; Comedy